Her2-Targeted Multifunctional Nano-Theranostic Platform Mediates Tumor Microenvironment Remodeling and Immune Activation for Breast Cancer Treatment - Zheng D (Dove Medical Press, 2020)
Dongdong Zheng,1,* Caifeng Wan,1,* Hong Yang,2 Li Xu,1 Qi Dong,1 Chengrun Du,3 Jing Du,1 Fenghua Li1 1Department of Ultrasound, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2College of Chemistry and Materials Science, Shanghai Normal University, Shanghai, People’s Republic of China; 3Department of Radiation Oncology, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Du; Fenghua Li Email beautydujing@163.com; fenghua-li@163.comPurpose: The treatment of breast cancer is often ineffective due to the protection of the tumor microenvironment and the low immunogenicity of tumor cells, leading to a poor therapeutic effect. In this study, we designed a nano-theranostic platform for these obstacles: a photothermal effect mediated by a gold shell could remodel the tumor microenvironment by decreasing cancer-associated fibroblasts (CAFs) and promote the release of doxorubicin (DOX) from nanoparticles. In addition, it could realize photoacoustic (PA)/MRI dual-model imaging for diagnose breast cancer and targeted identification of Her2-positive breast cancer.Methods: Her2-DOX-superparamagnetic iron oxide nanoparticles (SPIOs)@Poly (D, L-lactide-co-glycolide) acid (PLGA)@Au nanoparticles (Her2-DSG NPs) were prepared based on a single emulsion oil-in-water (O/W) solvent evaporation method, gold seed growing method, and carbon diimide method. The size distribution, morphology, PA/MRI imaging, drug loading capacity, and drug release were investigated. Cytotoxicity, antitumor effect, cellular uptake, immunogenic cell death (ICD) effect, and targeted performance on human Her2-positive BT474 cell line were investigated in vitro. BT474/Adr cells were constructed and the antitumor effect of NPs on it was evaluated in vitro. Moreover, chemical-photothermal therapy effect, PA/MRI dual-model imaging, ICD effect induced by NPs, and tumor microenvironment remodeling in human BT474 breast cancer nude mice model were also investigated.Results: Nanoparticles were spherical, uniform in size and covered with a gold shell. NPs had a photothermal effect, and can realize photothermal-controlled drug release in vitro. Chemical-photothermal therapy had a good antitumor effect on BT474/Adr cells and on BT474 cells in vitro. The targeting evaluation in vitro showed that Her2-DSG NPs could actively target and identify Her2-positive tumor cells. The PA/MRI imaging was successfully validated in vitro/vivo. Similarly, NPs could enhance the ICD effect in vitro/vivo, which could activate an immune response. Immunofluorescence results also proved that photothermal effect could decrease CAFs to remodel the tumor microenvironment and enhance the accessibility of NPs to tumor cells. According to the toxicity results, targeted drug delivery combined with photothermal-responsive drug release proved that NPs had good biosafety in vivo. Chemical-photothermal therapy of Her2-targeted NPs has a good antitumor effect in the BT474 nude mice model.Conclusion: Our study showed that chemical-photothermal therapy combined with tumor microenvironment remodeling and immune activation based on the Her2-DSG NPs we developed are very promising for Her2-positive breast cancer.Keywords: tumor microenvironment remodeling, chemoimmunotherapy, photothermal effect, targeted nano-theranostic platform, dual-modal imaging